Robotic low anterior resection versus transanal total mesorectal excision in rectal cancer: A comparison of 115 cases. Issue 2 (February 2018) - Perez, Daniel; Melling, Nathaniel; Biebl, Matthias; Reeh, Matthias; Baukloh, Julia-Kristin; Miro, Jameel; Polonski, Adam; Izbicki, Jakob R.; Knoll, Belinda; Pratschke, Johann; Aigner, Felix
Abstract: Background: Robotic low anterior resection (RLAR) and transanal total mesorectal excision (TaTME) are novel surgical techniques for resection of rectal cancer. To our knowledge, no data exist on direct comparison of these procedures in terms of oncological or functional parameters. Methods: 60 RLAR and 55 TaTME for rectal cancer were compared in respect to patient characteristics, clinicopathological parameters, intraoperative and perioperative results and anatomopathological outcome. Results: 62 surgeries addressed tumors of the lower third (53.9%). No intergroup differences in terms of patient characteristics and clinicopathological parameters were observed. Operating time did not differ between groups (p = 0.312), nor did the perioperative complication rate (p = 0.176). Circumferential resection margin was wider in the RLAR than in the TaTME group (p < 0.001), while no differences were found in the remaining oncological parameters. Conclusion: Our study shows comparable results for RLAR and TaTME in rectal cancer treatment. Both procedures should be considered equally feasible for low rectal cancer cases and as an alternative to conventional anterior resections (open or laparoscopic). Furthermore, both techniques allow excellent oncological outcome especially in patients with anatomical limitations.